2020
DOI: 10.1002/fsn3.1832
|View full text |Cite
|
Sign up to set email alerts
|

The impact of quinoa flour on some properties of ayran

Abstract: Yogurt-style products are the most popular functional products in many countries. In some countries, drinkable fermented dairy products such as doogh, lassi, chaas, and ayran are prepared by adding water in yogurt. Fermented dairy products have many health benefits such as cholesterol lowering, gastrointestinal relief, probiotics, nutrient content, and immune stimulation (Marsh, Hill, Ross, & Cotter, 2014).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
3
6
0
Order By: Relevance
“…The use of various dietary fibers led to a change in pH values. This finding was consistent with that reported by Akkoyun and Arslan (2020). There was a minor increase in titratable acidity in various kefir samples (Table 3).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The use of various dietary fibers led to a change in pH values. This finding was consistent with that reported by Akkoyun and Arslan (2020). There was a minor increase in titratable acidity in various kefir samples (Table 3).…”
Section: Resultssupporting
confidence: 94%
“…Petri dishes were incubated at 37°C for 2–3 days. Developed colonies at the end of the incubation period were counted to determine the Lactobacilli count (Akkoyun & Arslan, 2020). M17 Agar was used to determine Streptococci count, and petri dishes were incubated at 37°C for 2 days (Nacheva, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…During storage, the acidity of fermented milk products increased depending on the activities of starter cultures and of the enzymes they produced (Akin & Ozcan, 2017). Similar results have been reported by many researchers (Akkoyun & Arslan, 2020; Ivanovska et al, 2018; Salwa et al, 2004). Baria et al (2020) reported no significant change in acidity in yogurts with black carrot concentrate added and in control yogurts, except for the 12th day of storage.…”
Section: Resultssupporting
confidence: 91%
“…Quinoa flour can also be fermented to make novel probiotic beverages and spoonable vegan products (Lorusso et al ., 2018; Karovičová et al ., 2020; Väkeväinen et al ., 2020). In addition, quinoa can also be used for the development of nutritious and healthy fermented dairy products such as set‐type yogurt, stirred yogurt and other dairy‐based products such as Aryan and Kishk (Curti et al ., 2017; Abd‐Rabou et al ., 2020; Akkoyun, & Arslan, 2020; Mabrouk, & Effat, 2020). Due to the quality and nutritional value of their proteins, quinoa seeds are considered a new source of functional foods such as low glycaemic index quinoa milk and protein‐enriched pasta (Pineli et al ., 2015; Gupta et al ., 2021).…”
Section: Antinutritional Factorsmentioning
confidence: 99%